Natural organic matter in water : characterization and treatment methods - Sillanpaa, Mika E. T. (Butterworth-Heinemann, 2015)
Approximately 77 percent of the freshwater used in the United States comes from surface-water sources and is subject to natural organic matter contamination according to the United States Geological Survey. This presents a distinct challenge to water treatment engineers. An essential resource to breakthroughs in the characterization, treatment and removal of natural organic matter (NOM) from drinking water, this book focuses on advance filtration and treatment options, and processes for reducing disinfection byproducts. Topics include: characterization of NOM including: general parameters, isolation and concentration, fractionation, composition and structural analysis and biological testing; removal methods such as inorganic coagulants, polyelectrolytes and composite coagulants; electrochemical and membranes removal methods such as: electrocoagulation, electrochemical oxidation, microfiltration and ultrafiltration, nanofiltration and membrane fouling. --